EFFECT OF BIO-FUNGICIDES ON SEED QUALITY PARAMETERS ARAMETERS AND DISEASE CONTROL IN CHILLI SEEDS INFECTED WITH COLLETOTRICHUM CAPSICI - PRIYA REDDY,; Y.N., JAKHAR,; S.S,; O.S. DAHIYA, (The Bioscan, 2019)
Fruit rot caused by Colletotrichum capsici is the major constraint for production and marketability of chilli. Continuous use of chemical fungicides like carbendazim for effective control leads to negative impact on environment, soil and human health. Therefore, we evaluated the efficacy of bio-fungicides in comparison with carbendazim in chilli seeds infected with Colletotrichum capsici for seed germination, seedling vigour and disease incidence.Seed germination was high in Trichoderma viridae and carbendazim treatments in blotter and pot experiments respectively. Seedling length was significantly high in Trichoderma viridae treatment while, the seedling dry weight and seedling vigour index were significantly high in carbendazim treatment both in blotter method and pot culture. However, the seedling vigour with Trichoderma viridae was on par to the carbendazim, with equal weightage to seed germination, seedling length and dry weight in SVI calculations. The disease incidence was significantly low in Pseudomonas fluorescens treatment as compared to the carbendazim in blotter method. While in pot culture, T. viridae + P. fluorescens treatment was effective in controlling the fungal infection. Therefore, Trichoderma viridae or in combination with Pseudomonas fluorescens can be effectively used for seed treatment to control Colletotrichum capsici as an alternative to carbendazim.